Analisis Pengaruh Strategi Positioning Terhadap Keputusan Pembelian Produk Herbal Nutrend - Pangestu, Jessica A. A. (JURNAL RISET BISNIS DAN MANAJEMEN, 1996)
This study aims to test whether there is an influence positioning strategy variable consisting of product quality, product usage, and product prices on consumer purchasing decisions. The results of multiple linear regression analysis showed that the positioning strategy has significant positive effect on consumer purchasing decisions herbal health products Nutrend (studies on herbal consumers PT. Nutrend International in Manado City). Quality Products (Product Quality) has a positive effect. Positive effect on product usage. Positive effect on product prices. From these results it can be seen that the most dominant variable influencing purchasing decisions is a variable priced products. Keywords: Product Quality, Use of Product, Product Price and Consumer Purchase Decision